Maternal Alexithymia and Attachment Style: Which Relationship with Their Children’s Headache Features and Psychological Profile? - Tarantino, Samuela; Papetti, Laura; De Ranieri, Cristiana; Boldrini, Francesca; Rocco, Angela Maria; D’Ambrosio, Monica; Valeriano, Valeria; Battan, Barbara; Paniccia, Maria Francesca; Vigevano, Federico; Gentile, Simonetta; Valeriani, Massimiliano (Frontiers in Neurology, 2018)
Introduction. A growing body of literature has shown an association between somatic symptoms and insecure “attachment style”. In a recent study, we found a relationship between migraine severity, ambivalent attachment style and psychological symptoms in children/adolescents. There is evidence that caregivers’ attachment styles and their way of management/expression of emotions can influence children’s psychological profile and pain expression. To date, data dealing with headache are scarce. Our aim was to study the role of maternal alexithymia and attachment style on their children’s migraine severity, attachment style and psychological profile. Materials and methods. We enrolled 84 consecutive patients suffering from migraine without aura (female: 45, male: 39; mean age 11.8 ± 2.4 years). According to headache frequency, children/adolescents were divided in two groups: 1) high frequency (patients reporting from weekly to daily attacks), and 2) low frequency (patients having ≤ 3 episodes per month). We divided headache attacks intensity into two groups (mild and severe pain). SAFA “Anxiety”, “Depression” and “Somatization” scales were used to explore children’s psychological profile. To evaluate attachment style, the semi-projective test SAT for patients and ASQ Questionnaire for mothers were employed. Maternal alexithymia traits were assessed by TAS-20. Results. We found a significant higher score in maternal alexithymia levels in children classified as “ambivalent”, compared to those classified as “avoiding” (Total scale: p= 0.011). A positive correlation has been identified between mother's TAS-20 Total Score and the children's SAFA-A Total Score (p=0.026). In particular, positive correlations were found between maternal alexithymia and children's "Separation anxiety" (p=0.009) and "School anxiety" (p=0.015) subscales. Maternal "Externally-oriented thinking" subscale correlated with children’s school anxiety (p=0.050). Moreover, we found a correlation between TAS-20 Total Score and SAFA-D “Feeling of guilt” subscale (p=0.014). Our data showed no relationship between TAS-20 and ASQ questionnaires and children’s migraine intensity and frequency. Conclusions. Maternal alexithymia and attachment style have no impact on children's migraine severity. However, our results suggest that, although maternal alexithymic traits have no causative roles on children’s migraine severity, they show a relationship with patients’ attachment style and psychological symptoms, which in turn may impact on migraine severity.